Computational analysis of fine droplet in swirl injector for desalination. (2022) - Joe Patrick Gnanaraj, S.; Arulraj, I.; Appadurai, M.
Abstract: Desalination refers to a water treatment process that removes salts from water. Low Pressure Flash Evaporation desalination (LPFE) process is conducted experimentally with using of high flow swirl injector. This injector is used to improve the efficiency of the plant. The effects of atomizer's dimensions and flow parameters were studied and analyzed to get desirable droplet size and good yield. From this parametric study, we can know that droplet diameter effects yield. The theoretical results shows that droplet size should be in the range of 0.9 to 1.0 mm to get maximum yield.The internal flow behavior in high flow swirl injector also studied using a commercial computational fluid dynamics (CFD) software - FLUENT. Through these works, designed a swirl nozzle at high flow rate (1lit/s) with parameter's study and optimized technically. This paper deals, through CFD analysis that desirable range of droplet size is analyzed and has been proved that to get maximum yield with the effect of various flow parameters. The result gives a valuable output for developing technology in desalination.